2017
DOI: 10.1186/s12906-017-1702-7
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-induced effects of extract from Artemisia annua Linné by modulating PTEN/p53/PDK1/Akt/ signal pathways through PTEN/p53-independent manner in HCT116 colon cancer cells

Abstract: BackgroundThe extracts from Artemisia annua Linné (AAE) has been known to possess various functions including anti-bacterial, anti-virus and anti-oxidant effects. However, the mechanism of those effects of AAE is not well known. Pursuantly, we determined the apoptotic effects of extract of AAE in HCT116 cell. In this study, we suggested that AAE may exert cancer cell apoptosis through PTEN/PDK1/Akt/p53signal pathway and mitochondria-mediated apoptotic proteins.MethodsWe measured 3-(4,5-dimethylthiazol-2-yl)-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 33 publications
(24 reference statements)
0
19
0
Order By: Relevance
“…Another study conducted by Worku et al reported the cytotoxic effect of this extract on solid tumor cell lines such as prostate cancer cells 20 . Moreover, Eun Ji Kim indicated that AAE could exert an apoptotic effect on colon cancer cells 21 . In an effort to investigate the potential therapeutic value of AAE, for the first time, we aimed to evaluate the restrictive effect of methanolic extract from aerial parts of Artemisia annua on both Nalm-6 and Reh cell lines alone and in combination with VCR.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Worku et al reported the cytotoxic effect of this extract on solid tumor cell lines such as prostate cancer cells 20 . Moreover, Eun Ji Kim indicated that AAE could exert an apoptotic effect on colon cancer cells 21 . In an effort to investigate the potential therapeutic value of AAE, for the first time, we aimed to evaluate the restrictive effect of methanolic extract from aerial parts of Artemisia annua on both Nalm-6 and Reh cell lines alone and in combination with VCR.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the loss of PDK1 in the developing dentate gyrus causes unbalanced cell proliferation and neurogenesis [32]. A growing amount of evidence suggests that PDK1 is upregulated in cancer cells and required for cell survival [33][34][35]. All these studies demonstrate that PDK1 plays different roles during different biological processes.…”
Section: Introductionmentioning
confidence: 64%
“…Kim et al [34] evaluated the effect of an A. annua extract on human colon cancer cell line HCT116 and found that cell cycle arrest occurred at the G 1 /S phase mediated by the Akt/mTOR pathway. Later on, they demonstrated that A. annua extract induced apoptosis through the regulation of specific proteins such as Bax, Bak, and cytochrome c in PDK1/Akt signaling pathways via a PTEN/p53-independent manner [35]. In this work, cell cycle analysis suggested that a modified cellular distribution in different phases of the cycle occurred in the treated cells and that the sub-G1 peak observed was due to cellular debris rather than fragmented DNA, which is typical of apoptosis.…”
Section: Discussionmentioning
confidence: 99%